2017
DOI: 10.1073/pnas.1707279114
|View full text |Cite
|
Sign up to set email alerts
|

Survival and divergence in a small group: The extraordinary genomic history of the endangered Apennine brown bear stragglers

Abstract: Survival and divergence in a small group: the extraordinary genomic history of the endangered Apennine brown bear stragglers 2 AbstractAbout 100 km east of Rome, in the Central Apennine mountains, a critically endangered population of approximately fifty brown bears live in complete isolation. Mating outside this population is prevented by several hundred kilometers of bear-free territories. We exploited this natural experiment to better understand the gene and genomic consequences of surviving at extremely s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
132
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 82 publications
(77 reference statements)
13
132
0
Order By: Relevance
“…This finding is consistent with Korsten et al () and Anijalg et al () who postulated that clade 3a1 experienced a widespread westward expansion after LGM across northern Eurasia and had more western distribution. Our microsatellite and mtDNA data, coupled with a recent genomic study of brown bear in Western and Central Europe (Benazzo et al, ), showed a complex scenario for the Western Carpathians. The initial colonization of the Western Carpathians by brown bears possessing mtDNA from subclade K of the Eastern lineage could have occurred during the late LGM as shown in Figure d of Anijalg et al ().…”
Section: Discussionsupporting
confidence: 70%
“…This finding is consistent with Korsten et al () and Anijalg et al () who postulated that clade 3a1 experienced a widespread westward expansion after LGM across northern Eurasia and had more western distribution. Our microsatellite and mtDNA data, coupled with a recent genomic study of brown bear in Western and Central Europe (Benazzo et al, ), showed a complex scenario for the Western Carpathians. The initial colonization of the Western Carpathians by brown bears possessing mtDNA from subclade K of the Eastern lineage could have occurred during the late LGM as shown in Figure d of Anijalg et al ().…”
Section: Discussionsupporting
confidence: 70%
“…The sustained negative population trends during the Holocene probably contribute to the signals of recent bottlenecks, such as reduced X/A ratios and high Tajima's D values that all populations show. Additionally, even the most diverse populations show values of genetic diversity similar to that of the severely bottlenecked Apennine brown bear (Benazzo et al, ), and only twice that of the extremely eroded sister‐species—the Iberian lynx (θ = 2.22 × 10 −4 , π = 2.6 × 10 −4 ; Abascal et al, ), whose values are comparable to the least diverse Eurasian lynx populations (Figure ). Still, differences in recent demography between populations, with European populations experiencing a severe reduction in population size throughout the Holocene and Asian populations usually maintaining a softer population decline, are reflected in current genetic patterns: European populations, especially westernmost ones, show larger genetic differentiation, increased drift parameters in treemix analysis, along with bottleneck signals and lower genome diversity.…”
Section: Discussionmentioning
confidence: 87%
“…This Appennine endemic subspecies appears to be deeply distinct from the other European populations from a morphological point of view (Colangelo et al 2012b), while showing a genetic affinity between the remnant and isolated population of the other southern European populations (Swenson et al, 2011). However, Benazzo et al (2017) on the basis 26 of genomic analyzes have indicated a separation of the Apennine bears, from the rest of the other bear populations, of about 1500 years. The authors conclude that Apennines bear population represents a divergent evolutionary lineage.…”
Section: Cold Casesmentioning
confidence: 90%